Avaliação do padrão eletromiográfico dos músculos da mastigação em indivíduos com e sem DTM - Gonzalez, Tabajara de Oliveira (2009)
Eletromyographic evaluation of the chewing muscles is amply used in accompaniment of patients with temporomandibular disorders (TMD) with purpose of identifying EMG variations between symptomatic and asymptomatic individuals. However, they re missing studies that deal with parameters of Eletromiographic sign which are able to differentiate individuals with TMD from asymptomatic ones. To contribute to the function of Eletromyographic sign at the differentiation of individuals that present TMD signs and symptoms and asymptomatic ones, two studies were developed. The first study had as objective to categorize individuals with or without TMD signs and symptoms through the Fonseca s Anamnesis Index and to relate this classification to the age, stature, corporal weight and to the RMS values of Eletromyographic sign of masseters and anterior temporalis muscles at rest. 33 female volunteers were selected with the age of 17 to 23 (20,73 ± 1,20), evaluated by Fonseca s Anamnesis Index and divided in two groups: one of them without TMD signs and symptoms (s/TMD) consisting of 16 volunteers and the other group classified as TMD by the referred questionnaire, consisting of 17 volunteers. All these volunteers were submitted to the Eletromyographic evaluation of masseter and anterior temporalis muscles in both sides during the postural position at rest. They were weighted, measured the statures and noted the ages. Among the volunteers of the TMD group, there is a higher prevalence of a light degree TMD, there isn t a relation between the RMS averages of EMG of the studied muscles and a classification of the individuals by the Fonseca Index, the volunteers of TMD group presented higher prevalence of pain, chewed muscles tiredness, articulate noise and habit of grind or press teeth; only the corporal weight presents positive relation with the TMD severity. The second study had as objective to analyze the variability of Eletromyographic signs collected at rest, in bilateral isotonic chewing and in isometric of masseter and anterior temporalis muscles, to evaluate the electric activity of the muscles studied by the Asymmetric Index proposed by literature and to suggest a rate calculation between temporal electric activity in relation to masseter one, in attempt to differentiate the TMD individuals from s/TMD. Eletromiographic signs were collected when jaws at rest, bilateral isometric and bilateral isotonic chewing of the same 33 volunteers that participated in the first study, divided in TMD and s/TMD groups. It was analyzed the variability of the collected signs and applied the Asymmetric Index proposed by literature, besides the rate between temporal muscles and masseter suggested by the authors, in both groups studied. Individuals of TMD group presented a higher variability at EMG of the muscles studied in three collects realized, but it was only observed a significant difference in a collect at the postural position at rest (p≤0,05); only the rate calculation between the RMS values of temporal muscles and masseters, proposed in this study, was able to differentiate individuals with TMD from the asymptomatic ones (p≤0,0001), so this could be a future alternative at differentiation of individuals with or without TMD.